Dancing bodies of devotion : fluid gestures in Bharata natyam - Zubko, Katherine C. (Lanham, Maryland : Lexington Books, 2014)
This ethnography examines how contemporary dancers of Bharata Natyam, a traditionally Hindu storytelling dance form, embody Buddhist, Muslim, Christian and Jain narratives. These dancers choreographically adapt various religious identities and ideas in order to emphasize pluralistic cultural and ethical dimensions in their work. Through the dancing body, multiple religious and secular interpretations are able to co-exist.
Includes bibliographical references and index.
Print version record.
Keywords: Bharata natyam; Dance -- Religious aspects; GAMES -- Reference; GAMES -- Travel Games; Bharata natyam; Dance -- Religious aspects; Electronic books; Electronic books